Building Character and Competence Through a Philosophical Approach - Hasnah Faizah; Rionar Rambe; Riza Purnama Sari; Ruth Devi Elisa Putri; Rini Aulia (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study examines character and competency development through a philosophical approach. This philosophical approach plays a crucial role in developing students' character and competency, ensuring that education is not solely oriented toward knowledge but also toward the formation of morals and a holistic personality. This study employed a descriptive qualitative method, examining the ontological, epistemological, and axiological dimensions within the context of character education. The results indicate that a philosophical approach provides a profound understanding of the nature of humans as moral and rational beings capable of internalizing good values ​​through reflection. This approach also encourages students to think critically, be responsible, and demonstrate integrity in all their actions. Furthermore, spiritual and social aspects are strengthened through the development of empathy, wisdom, and ethical awareness in interactions with the environment. The application of a philosophical approach makes the educational process more meaningful because it touches on the realms of knowledge, morals, and spirituality in a balanced manner. Thus, philosophy-based education can create individuals who are not only intellectually intelligent but also possess strong character, a reflective spirit, and are able to make a positive contribution to society.